United States Agency for International Development (USAID) Assistance in Dealing with India’s COVID-19 Pandemic - Hidayat, Muhammad Taufik; Sahide, Ahmad (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
This article aims to know the interest of the United States in helping India deal with the COVID-19 pandemic in terms of global governance. The research method used was qualitative, using the documentation method by collecting data through international journals, the official internet of USAID and Worldometer. The theory used in this research is the theory of neorealism. From 2020 to 2022, the world faced serious problems with COVID-19 worldwide, including the United States through USAID, to assist India in the fight against COVID-19. India has partnered with USAID for decades. During the COVID-19 pandemic, the United States also demonstrated its existence by assisting other countries, especially India, which later made India the largest recipient of aid in the South Asian region. The assistance provided by the United States during the COVID-19 pandemic was under the pretext of demonstrating its existence and maintaining its influence (power) as a world leader over countries in South Asia, especially India. This situation could launch a foreign political strategy the United States has planned to implement properly.